Macrowear and occlusal microwear on teeth of cave bears Ursus spelaeus and brown bears Ursus arctos: Inferences concerning diet - Pinto Llona, Ana C. (Elsevier, 2019)
Peer reviewed Cave bears Ursus spelaeus are known from many limestone caves throughout the European Pleistocene. Despite the enormous quantities of fossils unearthed, many aspects of the cave bear ecology are still little known. Cave bear remains appear almost always with an array of variously sized tooth punctures, and the evidence from tooth mark types and sizes at several cave bear sites studied here indicates that cave bears themselves were responsible for the scavenging modifications recorded at these cave bear-only sites. Anatomical evidence for cave bear diet indicates that they had a tough-plant based diet and in addition, their powerful front legs suggest an enhanced digging capability that has sometimes been thought to relate to digging for tubers. Dental microwear analysis (DMA) approaches fossil and extant diets by comparing tooth wear for animals of known diet with that shown by fossils. Scanning electron microscope micrographs were prepared and the microwear features were measured. The results show differences in wear patterns between brown bears and cave bears from several locations and chronologies across northern Spain. There is no indication that these cave bears ate tubers or any food contaminated by soil; but the dental microwear observed indicates that they had a greater degree of bone consumption compared with brown bears.